Assessment of Macular Function during Vitrectomy: New Approach Using Intraoperative Focal Macular Electroretinograms - Matsumoto, Celso Soiti (PLoS One, 2015)
PURPOSE: To describe a new technique to record focal macular electroretinograms (FMERGs) during vitrectomy to assess macular function. METHODS: Intraoperative FMERGs (iFMERGs) were recorded in ten patients (10 eyes) who undergo vitrectomy. iFMERGs were elicited by focal macular stimulation. The stimulus light was directed to the macular area through a 25 gauge (25G) glass fiber optic bundle. Background light was delivered through a dual chandelier-type light fiber probe. Focal macular responses elicited with combinations of stimulus and background luminances were analyzed. RESULTS: A stimulus luminance that was approximately 1.75 log units brighter than the background light was able to elicit focal macular responses that were not contaminated by stray light responses. Thus, a stimulus luminance of 160 cd/m(2) delivered on a background of 3 cd/m(2) elicited iFMEGs from only the stimulated area. This combination of stimulus and background luminances did not elicit a response when the stimulus was projected onto the optic nerve head. The iFMERGs elicited by a 10° stimulus with a duration of 100 ms and an interstimulus interval of 150 ms consisted of an a-, b-, and d-waves, the oscillatory potentials, and the photopic negative response (PhNR). CONCLUSIONS: Focal ERGs with all components can be recorded from the macula and other retinal areas during vitreous surgery. This new technique will allow surgeons to assess the function of focal areas of the retina intraoperatively.